Uncommon Valor : the Recon Company that Earned Five Medals of Honor and Included America's Most Decorated Green Beret. - Moore, Stephen L. (Naval Institute Press, 2018)
Uncommon Valor is a look into the formation and operation of an advanced Special Forces recon company during the Vietnam War.